An Empirical Investigation into the Roles of Price Discounts, Product Quality, and Service Quality in Shaping Generation Z Consumers Purchase Decisions in Makassar, Indonesia - Azis, Muhammad; Abadi, Ridfan Rifadly; Azis, Fajriani; Adriansyah; Kemalasari, Andi Anggi (MANDAR: Management Development and Applied Research Journal, 2025)
This study aims to empirically examine and analyze the effects of price discounts, product quality, and service quality on purchase decisions among Generation Z consumers in Makassar's retail market. The research urgency stems from the retail sector's vital role as a driver of domestic economic growth and the rapid shift in consumer behavior, particularly among Generation Z, who are digital natives characterized by technology-driven, consumption-oriented lifestyles. Using an associative quantitative approach, data were collected through surveys and literature reviews, and purposive sampling was used to select 100 Generation Z respondents (born between 1997 and 2012) who had made transactions in modern retail stores in Makassar. Data were analyzed using multiple regression with SPSS 25. The simultaneous test revealed that price discounts, product quality, and service quality collectively had a significant influence on purchase decisions. The coefficient of determination indicating that the model could explain 75.5% of the variation in purchase decisions. Partially, all three independent variables also had positive and significant effects. These findings suggest that improving discount strategies, product standards, and service performance can enhance purchasing decisions among Generation Z consumers in the retail industry